Directional turnover towards larger‐ranged plants over time and across habitats - Ingmar R. Staude; Henrique M. Pereira; Gergana N. Daskalova; Markus Bernhardt‐Römermann; Martin Diekmann; Harald Pauli; Hans Van Calster; Mark Vellend; Anne D. Bjorkman; Jörg Brunet; Pieter De Frenne; Radim Hédl; et al. (Ecology Letters, 2022)
Species turnover is ubiquitous. However, it remains unknown whether certain types of species are consistently gained or lost across different habitats. Here, we analysed the trajectories of 1827 plant species over time intervals of up to 78 years at 141 sites across mountain summits, forests, and lowland grasslands in Europe. We found, albeit with relatively small effect sizes, displacements of smaller‐ by larger‐ranged species across habitats. Communities shifted in parallel towards more nutrient‐demanding species, with species from nutrient‐rich habitats having larger ranges. Because these species are typically strong competitors, declines of smaller‐ranged species could reflect not only abiotic drivers of global change, but also biotic pressure from increased competition. The ubiquitous component of turnover based on species range size we found here may partially reconcile findings of no net loss in local diversity with global species loss, and link community‐scale turnover to macroecological processes such as biotic homogenisation.